Didecyldimethylammonium Chloride- and Polyhexamethylene Guanidine-Resistant Bacteria Isolated from Fecal Sludge and Their Potential Use in Biological Products for the Detoxification of Biocide-Contaminated Wastewater Prior to Conventional Biological Treatment - Nataliya Loiko; Oleg Kanunnikov; Dmitriy Serdyukov; Vladimir Axelrod; Eduard Tereshkin; Anastasia Vishnyakova; Yuriy Litti (Biology, 2022)
Toxic shock caused by the discharge of biocide-contaminated fecal sludge (FS) from chemical toilets to conventional wastewater treatment plants (WWTP) can be a major problem in activated sludge operation. It is necessary to develop new environmental approaches to mitigate the toxicity of biocides in order to avoid degrading the performance of WWTP. “Latrina”, a chemical toilet additive containing didecyldimethylammonium chloride and polyhexamethylene guanidine, is widely used in environmentally safe toilet complexes (ESTC) on Russian railway trains to deodorize FS and control microbial activity. In this work, seven biocide-resistant bacterial strains were isolated and identified from the FS of ESTC. The values of the minimum inhibitory and bactericidal concentrations of biocides for the isolated strains were 4.5–10 times higher than for the collection microorganisms. The bacterium Alcaligenes faecalis DOS7 was found to be particularly resistant to “Latrina”, the minimum inhibitory concentration of which was almost 30 times higher than recommended for ESTC. Biological products based on isolated bacterial strains proved to be effective for FS biodegradation under both aerobic and anaerobic conditions. The results of the biochemical oxygen demand test and the newly developed disk-diffusion bioassay confirmed that isolated strains contribute to reducing toxicity of biocidal agents in FS. Hyper-resistance, non-pathogenicity, and potential plant growth-promoting ability make A. faecalis DOS7 promising for use in various biological products for wastewater treatment and bioremediation of soils contaminated with biocides, as well as in agriculture to increase plant productivity.